PENGARUH PIJAT OKSITOSIN TERHADAP PENGELUARAN ASI PADA IBU NIFAS - Yusti, Eli; Normawati, Normawati (Journal of Midwifery Tiara Bunda, 2025)
Decreased breast milk production and breast milk secretion in the first days of childbirth can be caused by a lack of prolactin and oxytocin hormone production. This study aims to determine the effect of oxytocin massage on breast milk secretion in postpartum mothers at PMB Siti Suhartati, S.Tr.Keb. The research method used is descriptive Quasi Experiment, and Two Group Pretest Posttest design, which aims to determine breast milk secretion in postpartum mothers regarding the implementation of oxytocin massage in increasing breast milk secretion in postpartum mothers at PMB Siti Suhartati, S.Tr.Keb, in Bekasi City in 2022. The results of the study showed that respondents who did not undergo oxytocin massage did not experience an increase in breast milk secretion. Respondents whose breast milk secretion remained stable were 7 people (23.3%) and respondents whose breast milk production decreased were 8 people (26.7%). It can also be seen that respondents who underwent oxytocin massage experienced an increase in breast milk production, namely 15 people (50%), sig. value. <0.05 then the independent variable has a significant effect on the dependent variable. The conclusion is that there is an effect of oxytocin massage on breast milk production in postpartum mothers at PMB Siti Suhartati, S.Tr.Keb, in 2022 with a p value = 0.001 (p <0.05)